Phytochemical Constituents of Cissus oliveri growing in Pwani Region, Tanzania - Estomini, Fadhili S.; Nnungu, Stephen I.; Buriyo, Amelia S. (Tanzania Journal of Science, 2023)
Cissus oliveri (Engl.) Gilg ex Engl. is among the plant species of the family Vitaceae widely used in traditional medicine for management of different ailments. This study aimed at assessing the phytochemicals of C. oliveri parts in order to provide scientific validation for its use as a therapeutic agent. Qualitative analysis of water and ethanolic extracts was conducted by using standard methods and the results revealed that all the parts possess alkaloids, flavonoids, phenols and tannins. Similarly, glycosides and saponins were only present in leaf and root. Quantitative analysis performed by gravimetric and spectrophotometric methods showed that all parts contain alkaloids, phenol, and tannins in large quantities. The largest amount was found in leaf for alkaloids (6.47 ± 0.41 mg/g DW) and phenols (4.85 ± 0.90 mg/g DW) compared to stem and root. Alkaloid content was higher in root than in stem (P < 0.01), whereas phenol content was the same in root and stem (p > 0.05). Further, there was no significant difference in tannins content among all the plant parts assessed. The presence and quantities of active phytochemicals in C. oliveri call for further investigations on the bioactivities of the extracts and isolated chemical constituents for potential pharmacological applications.